Pengaruh Celebrity Endorser, Brand Image, Online Customer Review Dan E-Trust Terhadap Keputusan Pembelian pada Marketplace Shopee - Annisa Widilia Rahmawati; IBN Udayana; Bernadetta Diansepti Maharani (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
This study aims to determine (1) the influence of Celebrity Endorser on purchasing decisions (2) the effect of Brand Image on purchasing decisions (3) the influence of reviews on purchasing decisions (4) the effect of e-trust on purchasing decisions. The sample in this study amounted to 210 Generation Z respondents in D.I Yogyakarta who use the Shopee application. Data collection method using a questionnaire method using a sampling technique, namely non-probability sampling with purposive sampling technique. The reason for using the purposive sampling technique is because each sample has its own criteria that are in accordance with the phenomenon to be studied. The results showed (1) Partially Celebrity endorsers have no significant effect on purchasing decisions in the Shopee market place. (2) partially Brand Image has a significant effect on purchasing decisions in the Shopee market place. (3) partially Online customer reviews have no significant effect on purchasing decisions on the Shopee market place. (4) partially E-Trust has a significant effect on purchasing decisions on the Shopee market place. Keywords: Celebrity endorser, Brand Image, Online customer review, E-Trust, Shopee